Influence of the continuum determination method on the mean transmission in the Lyα forest - Torbaniuk, O. (Advances in Astronomy and Space Physics, 2016)
Determination of the initial flux, or continuum, in the quasar spectra prior to its absorption by the intergalactic Hi is nontrivial problem and it affects the precision of the mean transmission in the Lyα forest, F(z). The results of comparison of the F(z) values obtained using different methods of the continuum determination are presented in this paper. This analysis was conducted using the most complete compilation of the F(z) data from the literature. It was found that the values of the F(z) obtained with the manually determined continuum are systematically higher than those obtained from extrapolated continuum. The difference varies from 5% at z = 2 up to 33% at z = 4.5, respectively.